2014
DOI: 10.3920/qas2012.0186
|View full text |Cite
|
Sign up to set email alerts
|

Mycoflora, aflatoxigenic strains of Aspergillus section Flavi and aflatoxins in fish feed

Abstract: Commercial feedstuffs are an important component in a modern aquaculture industry. Mycotoxin contamination of fish feeds represents a hazard to aquatic animals and human health. This study aimed to determine the mycoflora, aflatoxigenic strains of Aspergillus section Flavi, and occurrence of aflatoxins in fish feed samples. A total of 86 fish feed samples consisting of pellet, extruder, and scramble samples were collected from feed processing industries and fish farms in Iran. Identification of fungi, in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Similarly, Marijani et al [ 33 ] reported higher mean levels (>90.1 µg/kg) and ranges (<2.0–806.9 µg/kg) in fish feeds from the Lake Victoria region in Kenya than in the current study possibly due to a lower LOD of 2 µg/kg. Other authors have reported varied prevalences, levels and ranges of various AFs in fish feed from different parts of the world [ 29 , 34 , 62 , 81 , 82 , 83 ]. In another study, Marijani et al [ 34 ] have reviewed the toxic effects of AFs reported in assorted fish species ranging from reduced weight gain, reduced liver function to fish mortalities.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Marijani et al [ 33 ] reported higher mean levels (>90.1 µg/kg) and ranges (<2.0–806.9 µg/kg) in fish feeds from the Lake Victoria region in Kenya than in the current study possibly due to a lower LOD of 2 µg/kg. Other authors have reported varied prevalences, levels and ranges of various AFs in fish feed from different parts of the world [ 29 , 34 , 62 , 81 , 82 , 83 ]. In another study, Marijani et al [ 34 ] have reviewed the toxic effects of AFs reported in assorted fish species ranging from reduced weight gain, reduced liver function to fish mortalities.…”
Section: Discussionmentioning
confidence: 99%
“…The significant difference observed between the AF and AFB 1 concentrations in kanga and tilapia which are both farmed in the same pond also confirmed the hypothesis that the metabolic activities involved in the storage and/or elimination of mycotoxins in fish tissue vary with the fish species. The presence of AFs and AFB 1 in fish farmed in Cameroonian localities is of greatest concern because they can lead to negative effects on the development of fish such as stunting, liver damage, immunosuppression [ 26 ], decrease in growth performance, and increase susceptibility to disease and high mortality [ 27 ]. Rahman et al [ 28 ] pointed out the significant reductions in the total serum proteins, albumins, and globulins caused by the presence of AFB 1 in Nile tilapia.…”
Section: Discussionmentioning
confidence: 99%
“…Mngadi et al [ 3 ], also mentioned similar ratios in preliminary work done on South African animal feeds. Such variations may be attributed to the complex differences in the aetiology in the production of the toxins with a generally accepted understanding that AFB 1 and AFB 2 are produced by fungal species belonging to the A. flavus while A. paraciticus produces all the principal four AFs (AFB 1 , AFB 2 , AFG 1 and AFG 2 ) [ 18 , 19 , 20 , 21 ]. Moreover, experimental studies on the issue indicate that AFB and AFG ratios are largely influenced by conditions within ecological niches that parent fungal species occur [ 16 ].…”
Section: Discussionmentioning
confidence: 99%